2005
DOI: 10.12921/cmst.2005.11.02.141-146
|View full text |Cite
|
Sign up to set email alerts
|

Shall we worry about Packet Reordering?

Abstract: The article describes the recent standardisation initiatives for packet reordering metrics in IP networks, the methods of measuring it and also provides a discussion of the common factors affecting ordered packet delivery, based on real examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Bennett et al [30] refuted the widely held belief that packet reordering in the Internet is an uncommon behavior caused by incorrect or malfunctioning network components. Przybylski et al [31] discussed the factors affecting ordered packet delivery and revealed that the main protocols of modern gigabit networks cannot cope well with reordering.…”
Section: Related Workmentioning
confidence: 99%
“…Bennett et al [30] refuted the widely held belief that packet reordering in the Internet is an uncommon behavior caused by incorrect or malfunctioning network components. Przybylski et al [31] discussed the factors affecting ordered packet delivery and revealed that the main protocols of modern gigabit networks cannot cope well with reordering.…”
Section: Related Workmentioning
confidence: 99%
“…Also should a larger GOF rate be utilised, then SD will provide data equality for all frames within the GOF. In [11], the authors highlight that datagrams of dissimilar processing times, produce dissimilar transmission times. Such that by maintaining such datagram byte-size equality, the order of packet delivery is improved.…”
Section: Section Distributionmentioning
confidence: 99%
“…In Juniper M160, with four parallel processors, each with a capacity of 2.5 Gbps to serve a single 10Gbps interface, reordering was a concern [13,14]. Corrective action was taken in the design of the subsequent generations of high-end Juniper routers, e.g., T640, to avoid this problem.…”
Section: A Routersmentioning
confidence: 99%
“…Corrective action was taken in the design of the subsequent generations of high-end Juniper routers, e.g., T640, to avoid this problem. Other notable instances of reordering include that in BD6808/6816 [14]. The recent high-end routers attempt to reduce or avoid reordering by either a) input buffering, i.e., tracking the packets at the input to identify the individual streams, and forwarding the packets of the same stream to the same queue, thus preventing reordering, or b) output buffering, i.e., buffering packets at the output of the router to ensure that the packets belonging to the same stream are released in the order of their entry into the node [15].…”
Section: A Routersmentioning
confidence: 99%